Efficient Cleavage of Lignin Model Compounds into Phenols and Aldehydes over NiOOH Catalyst. Issue 19 (28th July 2022) - Mei, Xuelei; Liu, Huizhen; Wu, Haihong; Wu, Wei; Zheng, Bingxiao; Zhang, Kaili; Xu, Caiyun; Xu, Jiao; He, Mingyuan; Han, Buxing
Abstract: The highly‐efficient utilization of lignin and its derivatives is of great importance. Phenylacetaldehyde, as an important industrial raw material, is rarely reported to be directly obtained from biomass sources via thermal catalytic transformation. In this work, we found that NiOOH catalyst could efficiently catalyze the cleavage of β‐O‐4 lignin model compound to phenylacetaldehyde and phenol in water without need of any exogenous hydrogen. The catalytic mechanism study indicates that NiOOH could catalyze the elimination of Cα −OH to form an enol ether intermediate, which is then hydrated to phenylacetaldehyde and phenol. Abstract : Sustainable chemistry : Phenylacetaldehyde, as an important industrial raw material, is rarely reported to be directly obtained from biomass sources via thermal catalytic transformation. In this work, we found that NiOOH catalyst could efficiently catalyze the cleavage of β‐O‐4 lignin model compounds to phenylacetaldehyde and phenol in water without need of any exogenous hydrogen.